Strategic information planning: Insights from an action research project in the financial services industry - Rolf Alexander Teubner; Martin Mocker (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2005)
The core purpose of strategic information planning (SIP) lies in identifying future directions for investments in information technology, information systems and information supply that will assist an organisation to realise its business goals. SIP is a critical challenge and major concern to both academics and practitioners, in particular consultants. While the latter have proposed a number of formal methodologies and principles of good practice, these are normative recommendations that are hardly justified through theoretical insight. In fact, SIP is yet to be well understood theoretically and requires more empirical support. This motivated us to carry out an in depth case study on SIP in a financial service company. The study aimed at improving the SIP practices in place and was conducted in an action research-like manner. This research report at hand presents the results of the study. We firstly describe the enterprise, its situation and the SIP practices in place. We then reflect upon the SIP process, its contingencies and its outcome in light of the current academic literature. This leads us to a number of theoretically informed suggestions that concern the improvement of SIP as well as the direction of the resulting information strategy. These suggestions have already been debated with senior IT executives from the case enterprise. This debate helped to confirm some theoretical propositions from literature while other recommendations were not agreed upon by the practitioners. Our findings from the study are finally framed to give a fresh impetus to future research and perhaps challenge some current wisdom.
Keywords: 650; Information (Technology/ Systems) Strategy; Strategic Information Systems Planning; Strategic Alignment; IS/IT Governance; IT/IS Balanced Scorecard; Information Infrastructure; Information Function; Finanzdienstleistung; Informationssystem; Strategisches Management